2016
DOI: 10.1002/mnfr.201600315
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion ofCitrusflavanones and their major catabolites after consumption of fresh oranges and pasteurized orange juice: A randomized cross-over study

Abstract: Despite 2.4-fold higher doses, excretion of flavanones from ingested fresh orange fruit did not differ from that following orange juice consumption, possibly due to a saturation of absorption or their entrapment in the fiber-rich matrix of the fruit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 36 publications
(92 reference statements)
8
84
0
Order By: Relevance
“…The few human feeding studies involving flavones available so far reported a low bioavailability for this phytochemical [18,46], which could be ascribable to the low absorption of flavones, as demonstrated in the present investigation. Conversely, several scientific data are available for naringenin and hesperetin absorption, and all studies agree about the importance of colonic microbiota activity on this class of (poly)phenols [47,48,49]. The absorption curves observed in the present work confirm that flavanone metabolism principally occurs in the large intestine.…”
Section: Discussionsupporting
confidence: 80%
“…The few human feeding studies involving flavones available so far reported a low bioavailability for this phytochemical [18,46], which could be ascribable to the low absorption of flavones, as demonstrated in the present investigation. Conversely, several scientific data are available for naringenin and hesperetin absorption, and all studies agree about the importance of colonic microbiota activity on this class of (poly)phenols [47,48,49]. The absorption curves observed in the present work confirm that flavanone metabolism principally occurs in the large intestine.…”
Section: Discussionsupporting
confidence: 80%
“…Pharmacokinetics of narirutin after ingestion of orange juice in healthy humans were reported by Silveria et al [27] . The majority of oral intake-narirutin is considered to reach the colon, and colonic microbiota deglycosylate narirutin to naringenin, that is then absorbed by colonocytes [28] . Thus, it is considered that narirutin exists like a prodrug, and its aglycone naringenin works as an active form within the body.…”
Section: Discussionmentioning
confidence: 99%
“…However, short activity cessation slightly enhanced metabolites excretion [82]. In the same line, it was also shown that the urinary metabolites excretion does not differ after fresh oranges or pasteurized orange juice consumption, even if the latter contains about half of total flavanones amount [83].…”
Section: Bioavailability Of Naringeninmentioning
confidence: 99%